Political alignment and project funding - Luisa Schneider; Daniela Wech; Matthias Wrede (International Tax and Public Finance, 2022)
We analyze the relationship between the party affiliation of politicians at different levels of government and the spatial distribution of funding for research, development and innovation projects. In particular, we are investigating whether more federal grants are being granted in Germany for projects in federal states whose government is led by the same political party as the responsible ministry at federal level. Our dataset contains detailed information on publicly funded projects in Germany in the period 2010–2019. Using a fixed-effects estimation approach, we find a link between grant allocation and party affiliation of funding for research, development and innovation projects, in particular smaller ones. For these projects, political alignment is associated with an average increase in public funding by almost 10,000 euro. Our results suggest that public funds for research, development and innovation projects could be used more efficiently than they are.
Keywords: D72; R12; H77; 340; Project funding; Political alignment; Innovation policy; Regional policy; Intergovernmental relations; New public management